1987
DOI: 10.3758/bf03330288
|View full text |Cite
|
Sign up to set email alerts
|

Decisions following reading and bias in recall

Abstract: The role of decision making in biasing recall of prose was examined. Both making a decision subsequent to reading and encountering an experimenter-provided decision resulted in recall biased in the direction of the decision. Conditions in which subjects made their own decisions, however, resulted in greater levels of decision-congruent recall than did conditions in which the experimenters furnished decisions to subjects. In addition, the level of recall of incongruent information in the subject-made decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The results were robust in a variety of conditions introduced to undermine biased memory, including varying delay time and imposing a decision on the participants. Similar findings were reported by Timme, Corkill, and Glover (1987) in a short study about memory after reading. This leads to Hypothesis 1: Seniors are more likely to correctly recognize target sentences that are consistent with their prior decisions than sentences that are inconsistent with their prior decisions.…”
supporting
confidence: 90%
“…The results were robust in a variety of conditions introduced to undermine biased memory, including varying delay time and imposing a decision on the participants. Similar findings were reported by Timme, Corkill, and Glover (1987) in a short study about memory after reading. This leads to Hypothesis 1: Seniors are more likely to correctly recognize target sentences that are consistent with their prior decisions than sentences that are inconsistent with their prior decisions.…”
supporting
confidence: 90%
“…This pattern does not reflect a general tendency to recall decision-consistent information. Second, Dellarosa and Bourne's findings have been called into question by Timme, Corkill, and Glover (1987). In their replication of the study by Dellarosa and Bourne, they found that recall of decision-inconsistent material (as well as consistent material) was facilitated by making a decision about previously read material.…”
Section: Discussionmentioning
confidence: 97%